2018
DOI: 10.1007/s11356-018-1202-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster

Abstract: Insecticide resistance is a major challenge in successful insect pest control as the insects have the ability to develop resistance to various widely used insecticides. Butene-fipronil is a novel compound with high toxicity to insects and less toxicity to the non-target organisms. In the present study, the effect of butene-fipronil alone and in combination with three enzyme inhibitors, piperonyl butoxide (PBO), diethyl maleate (DEM), and triphenyl phosphate (TPP), was carried out on larvae and adults of Drosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…xanthotoxin-fed S. exigua might result from the ability of this plant allelochemical to induce detoxification enzymes, mainly cytochrome P450s. The increase in activity of detoxification enzymes seen here is consistent with previous studies, which showed a similar increase in activity of cytochrome P450s [12,29,32,60] in many polyphagous herbivorous insects exposed to plant secondary metabolites and insecticides. Because the synergist PBO can also inhibit nonspecific esterase activity [61], the effect of xanthotoxin intake on carboxylesterase and Glutathione S-Transferases and its corresponding contribution to the tolerance of pyrethroid insecticide to S. exigua larvae should be investigated in further study.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…xanthotoxin-fed S. exigua might result from the ability of this plant allelochemical to induce detoxification enzymes, mainly cytochrome P450s. The increase in activity of detoxification enzymes seen here is consistent with previous studies, which showed a similar increase in activity of cytochrome P450s [12,29,32,60] in many polyphagous herbivorous insects exposed to plant secondary metabolites and insecticides. Because the synergist PBO can also inhibit nonspecific esterase activity [61], the effect of xanthotoxin intake on carboxylesterase and Glutathione S-Transferases and its corresponding contribution to the tolerance of pyrethroid insecticide to S. exigua larvae should be investigated in further study.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Further studies show that different insecticide resistance mechanisms in S. litura, bemisia tabaci and Drosophila melanogaster were associated with the enhanced activity of cytochrome P450 monooxygenase (MFO) and esterase (Young et al 2006;Karuppaiah et al, 2017;Wang et al 2018). Mechanisms involved in P450 monooxygenase and esterase are also observed in butne-fipronil exposed D. melanogaster (Arain et al 2018). To our best knowledge, this is the first study of the sub lethal effects of lufenuron exposure on key biological traits and detoxification enzymes activity.…”
Section: Discussionmentioning
confidence: 78%
“…Although we experimentally determined the interaction between miR‐2b‐3p and cytochrome P450 ( CYP9f2 ), we have not provided direct evidence that CYP9F2 can metabolize deltamethrin or chlorantraniliprole and its role in the detoxification of these compounds in P. xylostella requires further investigation. However, previous studies have shown that the expression levels of CYP9F2 and other members of the CYP9 family increase following application of insecticides and that their transcript levels are significantly higher in resistant insects (Stevens et al ., ; Ghanim & Kontsedalov, ; Li et al ., ; Arain et al ., ). The ability of miR‐2b‐3p to decrease deltamethrin resistance in P. xylostella larvae makes this miRNA a good candidate to produce a transgenic plant for further investigation.…”
Section: Discussionmentioning
confidence: 97%